‘We can go anywhere’: Understanding independence through a case study of ride-hailing use by people with visual impairments in metropolitan India - Kameswaran, Vaishnav; Gupta, Jatin; Pal, Joyojeet; O’Modhrain, Sile; Veinot, Tiffany C.; Brewer, Robin N.; Parameshwar, Aakanksha; Y, Vidhya; O'Neill, Jacki (Computer Supported Co-operative Work (CSCW), 2018)
Ride-hailing services have received attention as part of the growing work around the sharing economy, but the focus of these studies has largely been on drivers. In this paper, we examine how ride-hailing is transforming the transportation practices of one group of passengers - people with visual impairments in metropolitan India. Through a qualitative study consisting of interviews and observations, we examined the use and impact of these services on our target population, who otherwise contend with chaotic, unreliable, and largely inaccessible modes of transportation.We found that ride-hailing services positively affects participants’ notions of independence, and we tease out how independence for our participants is not just about ‘doing things alone, without help’ but is also situated, social and relative. Furthermore, we show how accessibility, in the case of ride-hailing in India, is a socio-technical and collaborative achievement, involving interactions between the passenger, the driver, and the technology.
CSCW Best Paper